Dinamika Partisipasi Pemuda dan Transformasi Sosial Berbasis Masjid: Studi Kasus di Masjid Raya Gunung Tua - Abdul Fikri Ginting; Abdullah, Abdullah (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study aimed to analyze the forms and patterns of youth participation, the driving and inhibiting factors, as well as their contributions to da‘wah activities and social change at the Grand Mosque of Gunung Tua, Padang Lawas Utara Regency. The study employed a qualitative approach, with data collected through online interviews conducted via WhatsApp Chat and WhatsApp Call. The research participants included mosque youth, mosque administrators, and community leaders who were directly involved in da‘wah activities.The findings revealed that youth participation encompassed a wide range of roles, including attending Islamic study sessions, acting as mobilizers of da‘wah activities, and performing technical roles such as documentation, sound system management, and organizing committees. The patterns of youth participation varied, including consistent, situational, initiative-based, and responsive participation, which were influenced by personal interests, time availability, and communication patterns within the mosque organization. The driving factors of youth participation included religious motivation, social and family support, peer influence, and the openness of mosque administrators to youth ideas and creativity. Meanwhile, the inhibiting factors consisted of educational and occupational commitments, weak time management, limited attractiveness of activities, inadequate facilities, and low self-confidence. Overall, youth participation contributed significantly to social change through digital-based da‘wah innovations, social activities, youth development programs, and the strengthening of solidarity and the role of the mosque as a center for community empowerment.